Evaluation of Two Marking Methods for 1-day-old Northern Bobwhite Chicks - A. Vincent Carver; Loren W. Burger Jr.; Leonard A. Brennan (National Quail Symposium Proceedings, 2017)
We compared survival, weight gain, and mark retention of wing bands (n = 50), passive integrated transponders (PITs)(n = 50), and leg bands proportional to the chicks size (control) (n = 50) on 1-day-old northern bobwhite (Colinus virginianus) chicks. A repeated measures, generalized complete randomized block ANOV A of the weekly gain in weight showed no difference in the chicks growth (p >) 0.05). Survival was similar between marking methods (wing band, PITs, leg band, and control). Retention of bands during the twelve-week pen study were equal but 4% of PITs were destroyed when adult birds were recovered after harvest. We concluded that wing bands may be the most practical method of marking 1-day-old bobwhite chicks.